Die theologische Rezeption Kierkegaards im Überblick: Motive, Zusammenhänge und Polemiken - Šajda, Peter (Kierkegaard studies. Yearbook, 2025)
Kierkegaard as a thinker is hard to characterize, and it is debatable whether he can be classified as a theologian. Although his education was in theology, he did not pursue the path of an academic theologian, nor was he involved in ecclesial structures, and at the end of his life he even provoked an intense conflict with the leadership of the Church of Denmark. Nonetheless, his authorship experienced an extensive reception in theology and inspired numerous influential theologians from the Germanophone, Anglophone and Francophone world. In the present article, I first trace the early controversies about Kierkegaard’s theological legacy and subsequently map the complex reception in both Protestant and Catholic theology. I identify a variety of motifs and emphases that later theologians adopted from Kierkegaard highlighting the convergences and divergencies of their respective receptions. In my discussions I take into account the newest research provided by the project Kierkegaard Research: Sources, Reception and Resources.